Expression of TNF and TNF receptors (p55 and p75) in the rat brain after focal cerebral ischemia. - Botchkina, G. I. (The Feinstein Institute for Medical Research, 1997)
Cerebral ischemia induces a rapid and dramatic up-regulation of tumor necrosis factor (TNF) protein and mRNA, but the cellular sources of TNF in the ischemic brain have not been defined. The diverse activities of TNF are mediated via ligand interaction with two distinct receptors, p55 and p75, which activate separate intracellular signal transduction pathways, leading to distinct biological effects. Since the effects of cerebral ischemia on TNF receptor (TNFR) expression are unknown, we examined the cellular localization and protein expression of TNF and its two receptors in the rat cerebral cortex in response to permanent middle cerebral artery (MCA) occlusion. The results indicate that focal. cerebral ischemia up-regulates expression of TNF and both TNFRs within the ischemic cortex. The most abundant type of TNF immunoreactivity (IR) was a punctate and filamentous pattern of transected cellular processes; however, cell bodies of neurons, astrocytes, and microglia, as well as infiltrating polymorphonuclear (PMN) leukocytes also showed TNF IR. Brain vasculature displayed TNF IR not only within endothelial cells but also in the perivascular space. MCA occlusion induced significant up-regulation of TNF receptors, with p55 IR appearing within 6 hr, significantly before the appearance of p75 IR at 24 hr after the onset of ischemia. Since p55 has been implicated in transducing cytotoxic signalling of TNF, these results support the proposed injurious role of excessive TNF produced during the acute response to cerebral ischemia.